2008
DOI: 10.1111/j.1365-3113.2008.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics and temporal diversification of the earliest true flies (Insecta: Diptera) based on multiple nuclear genes

Abstract: Relationships among families of the lower Diptera (formerly suborder 'Nematocera') have been exceptionally difficult to resolve. Multiple hypotheses based on morphology have been proposed to identify the earliest lineages of flies and place the phylogenetic origin of the higher flies (Brachycera), but convincing support is limited. Here we resolve relationships among the major groups of lower Diptera using sequence data from four nuclear markers, including both ribosomal (28S rDNA) and protein-coding (CAD, TPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
171
4
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(193 citation statements)
references
References 50 publications
17
171
4
1
Order By: Relevance
“…These fly families include very few species, all of which have extreme morphological adaptations in both larval and adult stages for living in fast-flowing water. These morphological specializations have previously obscured their evolutionary relationships, although a recent molecular analysis hypothesizes the early divergence that we confirm here (11,12). The remaining lower Diptera is composed of the infraorders Tipulomorpha (crane flies), Culicomorpha (mosquitoes), Psychodomorpha (sand flies), and Bibionomorpha (march flies and gall midges) (11) (Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…These fly families include very few species, all of which have extreme morphological adaptations in both larval and adult stages for living in fast-flowing water. These morphological specializations have previously obscured their evolutionary relationships, although a recent molecular analysis hypothesizes the early divergence that we confirm here (11,12). The remaining lower Diptera is composed of the infraorders Tipulomorpha (crane flies), Culicomorpha (mosquitoes), Psychodomorpha (sand flies), and Bibionomorpha (march flies and gall midges) (11) (Fig.…”
Section: Resultssupporting
confidence: 53%
“…From numerous studies, we established a list of 457 putatively informative morphological characters to cover the anatomical diversity of Diptera. Team consultation reduced this to 371 external and internal morphological characters for larvae (93), pupae (11), and adults (267, including 55 head, 54 wing, 31 female genitalia, and 49 male genitalia). We scored 42 tier 1 dipteran taxa and 5 holometabolous outgroup taxa.…”
Section: Methodsmentioning
confidence: 99%
“…Mosquitoes (Diptera: Culicidae) form a monophyletic assemblage that is currently divided into two subfamilies (Anophelinae and Culicinae), 44 genera and >3500 species (Harbach and Kitching, 1998;Harbach, 2007;Bertone et al, 2008;Reidenbach et al, 2009). Typically, adult mosquitoes obtain nutrients for survival and reproduction from three sources (Clements, 1992;Foster, 1995): (1) teneral reserves from larval feeding on the microbiota and detritus in water, (2) nectar or other plant juices for energy, and (3) blood taken only by females for egg production.…”
Section: Introductionmentioning
confidence: 99%
“…This group also includes extinct families such as Grauvogeliidae (Lower/ Middle Triassic), Kuperwoodidae (Upper Triassic), Hennigmatidae (Lower Jurassic to Lower Cretaceous) and Nadipteridae (Lower/Middle Triassic to Lower Jurassic) (Krzemiński and Krzemińska, 2003;Shcherbakov et al, 1995). Recent phylogenetic studies based primarily on molecular data have found that Trichoceridae, Tipulidae, Nymphomyiidae, Deuterophlebiidae, Ptychopteridae and Blephariceridae are also among the most ancient lineages of the order (Bertone et al, 2008;Wiegmann et al, 2011). To date no phylogenetic study of Tanyderidae is existing, and its relationships within the family remain poorly understood; however, continued study of both fossil and extant species is likely to help in reconstructing the phylogeny.…”
Section: Discussionmentioning
confidence: 99%